DET METODISKE FORLØB: Kunst og håndværk i den antropologiske proces - Sjørslev, Inger (Tidsskriftet Antropologi, 1995)
Inger Sjørslev: The Course of Method: Art and Craft in the Anthropolocigal Process. A main point in this article is the assertion that anthropological method should be seen as a total process in which fieldwork cannot be separated from the process of working up the collected material implying analysis and final representation of a text. An additional argument concems the physical element in the process of recognition. The empirical basis for this is fieldwork on possession in the African-Brazilian religion Candomble, and the ensuing analysis and textual working up of the material. An illustrative analogy is drawn between the process of shaping and forming ethnographic material and the phenomenon of possession, which implies a process from interior diffuse and uncontrollable process, often leading to illness, to an exterior, delimited and controlled entity in the form of a spirit. On the basis of this, the article discusses the element of craft in anthropological method, and the possibility of making certain parallels to the process of creating a work of art.